2012
DOI: 10.1111/j.1472-765x.2011.03195.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of lager beer yeast in oxidative stability of model beer

Abstract: Aims:  In this study, we investigated the relationship between the ability of lager brewing yeast strains to tolerate oxidative stress and their ability to produce oxidative stable model beer. Methods and Results:  Screening of 21 lager brewing yeast strains against diamide and paraquat showed that the oxidative stress resistance was strain dependent. Fermentation of model wort in European Brewing Convention tubes using three yeast strains with varying oxidative stress resistances resulted in three model beers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 32 publications
0
19
1
Order By: Relevance
“…Furthermore, potent odourants like esters may act in synergy with other components affecting beer flavour in concentrations well below their threshold values (Meilgaard 1975a). However, each type of beer has its own prevailing aroma triggered either by the yeast strain (Nykanen and Nykanen 1977;Peddie 1990;Ramos-Jeunehomme et al 1991;Rossouw et al 2008) chosen or by parameters used during fermentation (Lodolo et al 2008;Saerens et al 2008a;Bravi et al 2009;Verbelen et al 2009;Blasco et al 2011;Berner and Arneborg 2012;Dekoninck et al 2012;Hiralal et al 2013). For example, while only isoamyl acetate (banana-like aroma) concentrations are above the threshold level in most lager beers, ales normally have ethyl acetate (solvent-like aroma) and ethyl hexanoate (apple-like aroma) as additional flavouring compounds with levels above the threshold (Meilgaard 1975b;Alvarez et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, potent odourants like esters may act in synergy with other components affecting beer flavour in concentrations well below their threshold values (Meilgaard 1975a). However, each type of beer has its own prevailing aroma triggered either by the yeast strain (Nykanen and Nykanen 1977;Peddie 1990;Ramos-Jeunehomme et al 1991;Rossouw et al 2008) chosen or by parameters used during fermentation (Lodolo et al 2008;Saerens et al 2008a;Bravi et al 2009;Verbelen et al 2009;Blasco et al 2011;Berner and Arneborg 2012;Dekoninck et al 2012;Hiralal et al 2013). For example, while only isoamyl acetate (banana-like aroma) concentrations are above the threshold level in most lager beers, ales normally have ethyl acetate (solvent-like aroma) and ethyl hexanoate (apple-like aroma) as additional flavouring compounds with levels above the threshold (Meilgaard 1975b;Alvarez et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies increasingly demonstrated that flavour stability of beer was highly determined by endogenous antioxidant activity of beer itself, thus numerous strategies, such as optimising brewing process, breeding oxidative stress-tolerant yeast strains and screening brewing materials with high antioxidant activity, have been practised to increase endogenous antioxidant activity for beer (Zhao et al, 2006(Zhao et al, , 2008Saison et al, 2010a;Berner & Arneborg, 2012;Jurkov a et al, 2012;Kunz et al, 2014). The endogenous antioxidants, including phenolic acids, sulphite, Maillard reaction products and some chelating agents, play vital roles in resisting oxidative damage and keeping flavour stability in beers (Vanderhaegen et al, 2006;Zhao et al, 2010Zhao et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Flavour deterioration of the packaged beer is affected by many factors, such as temperature , light , is stored, pH value , oxygen level , antioxidants , precursor concentration of key odorants and yeast loading . It has been widely accepted that the main factor responsible for beer flavour instability is the beer's antioxidant capacity during the aging process .…”
Section: Introductionmentioning
confidence: 99%